(3HjGf NWC YHO Gddg eMeO Hf ESeGYjd GdHNGQi aj JGQjNIs - (3YHO GdQMef Hf eMeO CHj MGJe GHf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO , GHf nCHj MGpJe , J (B327 (3g`s; (3GHf CHj MGJe , YHO GdQMef Hf eMeO CHj MGJe Hf GOQjS Hf GdefPQ GdJejej GdMfXdj GdQGRj, CHh eMeO,J (B327 (3g` s ((3CHh HcQ Hf Ydi Hf GSeGYjd GdHgfSi GdGfUGQi GdTGaYi s)
(3ChdgG (B:s
(3bGd GHh eMeO SeYJ CHj jbhd (B: (3bGd CHh RQYI GdN s
(3BNQgG (B:s
(3gPG BNQ eG CNQL ef HjGf NWC eMeO Hf GSeGYjd ai JGQjNg, Yf CHj RQYI hCHi MGJe QVi Gddg Yfge CLeYjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B324 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B170s
Keywords: (3GdJGQjNs